Situating Attention and Habit in the Landscape of Affordances - Elisa Magrì (Rivista Internazionale di Filosofia e Psicologia, 2019)
This paper aims to situate the roles of attention and habit in contemporary approaches to embodied cognition with particular regard to the conceptualisation of affordances. While Chemero has argued that affordances have a relational character that rules out dispositions, Rietveld and Kiverstein have suggested that engaging with affordances amounts to exercising skills. By critically reconsidering the distinction between dispositions and abilities proposed by Chemero, as well as the standard theory of habit that underpins accounts of skilful coping (including Rietveld’s and Dreyfus’), I propose to disambiguate habit from skill and to reassess the phenomenology of dispositions. Dispositions are motivational factors that depend on two elements: (i) sensitivity to context clues, which is regulated by habit and attention, and (ii) the positionality of the subject, which is inseparable from context-awareness. Drawing on Husserl’s and Merleau-Ponty’s insights, I argue that both (i) and (ii) can accommodate a dispositional view of affordances.